Criminal Law Policy in The Field of Fishery Based on Indonesia’s International Obligation - Marimin, Marimin; Setyawan, Lazarus Tri; Sularto, RB (Indonesian Journal of International Law, 2022)
The Indonesian Fisheries Law has determined criminal threats for perpetrators of illegal fishing in the ZEEI. In practice, there are differences in the application of imprisonment instead of fines for Indonesian citizens and foreign nationals who do illegal fishing. Such differences create injustice for Indonesian citizens. The results of the study indicate that criminal law policies in the field of fisheries need to be based on justice, in the sense of equality before the law. Foreign nationals who catch illegal fishing in the ZEEI are subject to imprisonment instead of a fine, while foreign nationals are not. Therefore, the Fisheries Law (especially Article 2013) needs to be amended by confirming the imposition of confinement instead of fines for all citizens who fish illegally in the ZEEI. Although the Fisheries Law adopted the 1982 UNCLOS, it did not emphasize the prohibition on the application of confinement instead of fines. In addition, Article 30 of the Criminal Code has also provided the basis for the imposition of confinement instead of fines. This change aims to provide a deterrent effect for perpetrators of illegal fishing in the ZEEI who have the status of foreign citizens. This objective is also in line with the premium remedial nature of criminal sanctions in the Fisheries Law. In addition, the abolition of the dualism of fisheries crime in the Fisheries Law also needs to be carried out and adjusted to the RUU-KUHP. All fishing crimes should be categorized as crimes.